Shared Paths to Well-Being: The Impact of Group Therapy - Elena Renée Sequeira-Nazaré; Bernhard Schmitz (Behavioral Sciences)
This study explored the impact of an art of living intervention within group psychotherapy for depression, focusing on constructs like life satisfaction, self-efficacy, and depression. Mental illness prevalence often exceeds available treatment options, particularly in Germany, where group psychotherapy is a viable alternative. While less researched, group therapy effectively improves well-being, especially through interpersonal exchange. Meta-analyses confirm cognitive behavioral group therapy’s effectiveness against depression, encouraging further investigation. This study employed a two-factor experimental design with randomized group allocation. The control group (CG) participated in weekly 50 min sessions for four weeks, while the experimental group (EG) received identical therapy plus reflective life-stimulating questions. Measures of depression, art of living, life satisfaction, and self-efficacy were taken before, after, and three months post-intervention. Among 107 participants, 52 were in the EG and 55 were in the CG. The results showed a significant 24% reduction in depression scores in the experimental group, a significant 16% increase in the art of living and a significant 19% increase in life satisfaction, while the CG showed no significant changes. Self-efficacy did not significantly improve in the EG. Follow-up data indicated sustained improvements in depression and art of living for the EG. The limitations of this study include a limited scope, practical constraints, randomization challenges and confounding variables, which are typical for experimental studies. These findings highlight the intervention’s potential, suggesting future research focusing on long-term effects, personality factors and disorder-specific applications.